Sosialisasi Bahaya Pernikahan Dini Dalam Upaya Penurunan Angka Stunting Di Desa Arul Relem Kecamatan Bies Kabupaten Aceh Tengah - Ramiati, Ramiati; Jaliansya, Agung; Alkahfi, Agung; Shahira, Destiamelia; Melala, Devi Maharani; Gustina, Era Maharani; Gustina, Julia; Jemiah, Jemiah; Azri, Maulana; Mauliyana, Mauliyana; Rahmatillah, Rahmatillah; Itawari, Risna; Mutuahmi, Sulis; Ningsih, Tri Adha; Usvani, Usvani; Yuliana, Yuliana (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
Stunting is a condition where a person's height is less than normal according to gender and age. This is due to the pattern of intake given to children starting from the first 1000 days of a child's life from birth so that children are shorter compared to children their age. Several factors that can influence stunting include infectious diseases, exclusive breastfeeding, early initiation of breastfeeding. At the time of early marriage, teenage women are psychologically not ready to become mothers. The lack of understanding of what stunting is and the dangers of stunting is what causes early marriage. This research aims to find out whether teenagers in Arul Relem Village, Bies District, Central Aceh Regency already know about the impact of early marriage on the risk of stunting in children. The research method used was a questionnaire with a pre-test and post-test and the data obtained could then be processed by calculating the average number of respondents who understood the material about early marriage and stunting before and after the socialization. The research results obtained after conducting outreach regarding the dangers of early marriage and stunting were 98%, which previously only reached 60%. From the average results of this calculation, it is very significant before the socialization is carried out and after the socialization is carried out.